2017
DOI: 10.1016/j.canlet.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 receptor 4 mediates renal cell carcinoma intravasation and metastasis

Abstract: Treatment options for metastatic renal cell carcinoma (RCC) are limited. In this study, we investigated impact of prostaglandin E2 (PGE2) receptor 4 (EP4) on RCC metastasis. We found that knockdown of EP4 in two RCC cell lines, ACHN and SN12C, does not affect xenograft tumor take or growth rate in mice, but reduces metastasis by decreasing tumor intravasation. Using chick chorioallantoic membrane (CAM) assay, we confirmed that blockade of EP4 signaling inhibits tumor intravasation. In vitro studies associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…5A ) cells to form tumors in mice. Equal number of viable cells were implanted orthotopically in the subrenal capsule space of one kidney 26 . Tumors were allowed to grow for 5 weeks before animals were sacrificed and organs (tumor-implanted and contralateral normal kidney, lymph nodes, lung, spleen, liver, and intestine) harvested.…”
Section: Resultsmentioning
confidence: 99%
“…5A ) cells to form tumors in mice. Equal number of viable cells were implanted orthotopically in the subrenal capsule space of one kidney 26 . Tumors were allowed to grow for 5 weeks before animals were sacrificed and organs (tumor-implanted and contralateral normal kidney, lymph nodes, lung, spleen, liver, and intestine) harvested.…”
Section: Resultsmentioning
confidence: 99%
“…Following the development of invasive behaviour, cancer cells undergo the second step of metastasis where they intravasate into blood vessels and lymphatics, which is promoted by inflammation through the production of mediators that increase vascular permeability [ 114 ]. Intravasation is regulated by MMPs [ 115 ], and PGE2 [ 116 ]. PGE2 can stimulate production of lymphangiogenic growth factors (VEGF-C and VEGF-D), which play important roles in regulating of the patency of collecting lymphatic vessels draining the tumour and facilitating metastasis [ 117 ].…”
Section: Inflammation-related Mechanisms In Cancer Pathogenesis Wmentioning
confidence: 99%
“…[12][13][14] Tumor metastasis is the main feature of malignant tumors and is often considered to be the most lethal property of tumors. 12,15 Metastasis is a complicated cell biological procedure that involves decreased adhesion between tumor cells, damages in extracellular matrix structure, movement of tumor cells, and formations of new blood vessels. 16,17 Meanwhile, tumor cells involve coordinated expression of various factors and then produce abundant hydrolytic enzymes that can degrade extracellular matrix and damage basement membrane, thus escaping from the basement membrane and migrating and colonizing in the distant organs.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Meanwhile, tumor cells involve coordinated expression of various factors and then produce abundant hydrolytic enzymes that can degrade extracellular matrix and damage basement membrane, thus escaping from the basement membrane and migrating and colonizing in the distant organs. 15,18 It was reported that the inhibition of tumor metastasis could remarkably enhance survival rates of tumor patients. 19 Octreotide (OCT) is a synthetic 8-peptide analog of somatostatin and mainly binds to somatostatin receptors that are overexpressed in a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%